2012
DOI: 10.1055/s-0032-1325376
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Pulmonary Venous Flow and Restrictive Foramen Ovale in Hypoplastic Left Heart

Abstract: Prenatal PV flow pattern and 2-DE of the FO size help in identifying the fetus at risk for neonatal EAS and patient selection for fetal cardiac intervention. Most late second trimester values will not change over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 21 publications
1
31
0
Order By: Relevance
“…Possible explanations for the difference in hospital mortality among in dominant LV and dominant RV might be: First, within the group of dominant RV sixteen of 19 (84.2%) urgent neonatal interventions were performed possibly accounting for the higher hospital mortality of patients with dominant RV. Second, prenatal detection of High‐risk HLHS had the worse neonatal outcome (23.5% hospital mortality), a finding that has been reported previously by our group and others . Third, altered prenatal right ventricular function, which has been recently elaborated, might also have a role in pre‐ and postintervention hospital mortality …”
Section: Discussionsupporting
confidence: 78%
“…Possible explanations for the difference in hospital mortality among in dominant LV and dominant RV might be: First, within the group of dominant RV sixteen of 19 (84.2%) urgent neonatal interventions were performed possibly accounting for the higher hospital mortality of patients with dominant RV. Second, prenatal detection of High‐risk HLHS had the worse neonatal outcome (23.5% hospital mortality), a finding that has been reported previously by our group and others . Third, altered prenatal right ventricular function, which has been recently elaborated, might also have a role in pre‐ and postintervention hospital mortality …”
Section: Discussionsupporting
confidence: 78%
“…Results of those studies suggest that ventricular remodeling with relatively reduced longitudinal, compared with circumferential, deformation that is observed after surgical palliation is detectable as early as fetal life. However, published data in this field are inconsistent, with differing strain and strain‐rate data. Additionally it has been shown that deformation parameters assessed by different ultrasound systems and software packages (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Postnatal strategies include compassionate care, single ventricle palliation or even heart transplantation with or without a hybrid procedure. Increasing detection rates of congenital heart disease (CHD) along with earlier diagnosis and subsequent prenatal management, advances in perioperative care and surgical technique have led to a decrease in mortality of children with HLHS such that prognosis of affected children has substantially improved. However, the long‐term outcome is influenced by altered right ventricular function.…”
Section: Introductionmentioning
confidence: 99%
“…These data are of paramount importance when planning intra‐uterine stenting of the inter‐atrial septum. Previously published series of patients with inter‐atrial stents in utero chose varying time frames for fetal intervention . According to our data, from a morphologic point of view, time frames of stent implantation should be fixed within the second trimester to prevent severe vascular/capillary proliferation and septal oedema in the developing lung, aiming for the delivery of more stable newborns with SAS/HLHS and I/HRAS …”
Section: Resultsmentioning
confidence: 99%